Does training location matter? Evidence from a randomized field experiment in Rural Indonesia - Ayu Pratiwi; Aya Suzuki (Agricultural and Food Economics, 2020)
Informal network helps disseminate agricultural knowledge in the rural area where formal extension is lacking. However, how the interplay between formal training and informal network promotes technology adoption is still under-studied. This paper aims to examine the effects of training locations upon knowledge and adoption of agricultural techniques via strengthened informal and formal social networks. We administer agricultural training of identical contents in farmers' hometown and in more remote but advanced locations and arrange farmers to travel to the respective locations. Then, we examine locational heterogeneity effects upon conservation and plant-rehabilitation techniques, and social network variables with formal extension services, informal network, and between participants and non-participants. Only farmers trained in the most remote location increase the size and depth of social network with their peers, extension expert, and non-participants upon returning from training. These changes in social networks may encourage them to adopt the technology. While formal training is important for knowledge diffusion, informal network is the key for successful adoption, and these networks are strengthened via training held in the most remote location.
Keywords: O1; O2; Q22; 330; Technology adoption; Sustainability; Impact evaluation; Social network; Information diffusion; Randomized controlled trial